A Tutorial Introduction to IoT Design and Prototyping with Examples - Meruje, Manuel (2020)
The dramatic drop in the price of computing hardware, coupled with the recent breakthroughs in embedded systems design that enabled the integration of high-level software and low-level electronics, have created a paradigm shift in embedded systems development. This has led to the development of different varieties of user-friendly Internet of Things (IoT) hardware development platforms for IoT prototyping. The ubiquity of such prototyping platforms has undoubtedly contributed towards the explosive growth of the IoT, which is already seeping into all areas of human endeavor, including transportation, logistics, business, and healthcare. Building IoT projects that can be controlled over the Internet can be challenging, especially for beginners. This chapter discusses the design and development of prototypes for IoT applications with focus on Arduino and Raspberry Pi platforms. The aim is to provide insightful information on best practices for designing and prototyping IoT projects, as well as to serve as step-by-step guidelines for beginners.